2012
DOI: 10.1186/1475-2859-11-10
|View full text |Cite
|
Sign up to set email alerts
|

Small surfactant-like peptides can drive soluble proteins into active aggregates

Abstract: BackgroundInactive protein inclusion bodies occur commonly in Escherichia coli (E. coli) cells expressing heterologous proteins. Previously several independent groups have found that active protein aggregates or pseudo inclusion bodies can be induced by a fusion partner such as a cellulose binding domain from Clostridium cellulovorans (CBDclos) when expressed in E. coli. More recently we further showed that a short amphipathic helical octadecapeptide 18A (EWLKAFYEKVLEKLKELF) and a short beta structure peptide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
90
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 85 publications
(93 citation statements)
references
References 29 publications
2
90
1
Order By: Relevance
“…19,21,22 Here, the amphipathic 18A (EWLKA-FYEKVLEKLKELF) short peptide was attached to the C-terminus of a nitrilase to investigate the formation of inclusion bodies and the impact this process had on the catalytic properties of the nitrilase.…”
Section: Formation Of Active Nitrilase Inclusion Bodies In E Coli Cellsmentioning
confidence: 99%
“…19,21,22 Here, the amphipathic 18A (EWLKA-FYEKVLEKLKELF) short peptide was attached to the C-terminus of a nitrilase to investigate the formation of inclusion bodies and the impact this process had on the catalytic properties of the nitrilase.…”
Section: Formation Of Active Nitrilase Inclusion Bodies In E Coli Cellsmentioning
confidence: 99%
“…8 Complexes of DNA and cationic proteins often result in polydisperse soluble aggregates probably derived from intrinsically disordered protein-protein interactions, 9,10 or in which the DNA itself plays a leading architectonic role, stabilizing aggregation-prone protein monomers in the form of monodisperse nanoparticles. 11 Self-assembling peptides that organize as different types of nanostructured materials, 12 promote unspecific aggregation when fused to larger proteins, 13,14 making them useless as fine architectonic tags. In summary, the rational de novo design of protein monomers with self-assembling activities has remained so far unreachable.…”
mentioning
confidence: 99%
“…This approach has been applied, for instance, to investigate the presence of functional proteins embedded in bacterial IBs [22-24]. Interestingly, in recent works it has been observed that the fusion of self-assembling or surfactant-like peptides to different proteins makes it possible to obtain active IBs, whose formation was detected in vivo monitoring the fluorescence of GFP - taken as a model system - fused to the peptide.…”
mentioning
confidence: 99%
“…Indeed, the bacterial cell images, obtained by confocal microscopy, showed a diffuse fluorescence when GFP was expressed alone, in a soluble form. When, instead, the GFP was expressed fused to the self-assembling or surfactant-like peptide, the fluorescence appeared localized in the cell, indicating the formation of active IBs [23,24]. Moreover the use of GFP tag as a reporter for corrected folding has been employed for the screening of AÎČ mutations and chemical compounds able to tune the aggregation propensity of the peptide.…”
mentioning
confidence: 99%